Analysis of in vitro osteoblast culture on scaffolds for future bone regeneration purposes in dentistry (2019)
One of the main focuses of tissue engineering is to search for tridimensional scaffold materials, complying with nature’s properties for tissue regeneration. Determining material biocompatibility is a fundamental step in considering its use. Therefore, the purpose of this study was to analyze osteoblast cell adhesion and viability on different materials to determine which was more compatible for future bone regeneration. Tridimensional structures were fabricated with hydroxyapatite, collagen, and porous silica. The bovine bone was used as material control. Biocompatibility was determined by seeding primary osteoblasts on each tridimensional structure. Cellular morphology was assessed by SEM and viability through confocal microscopy. Osteoblast colonization was observed on all evaluated materials’ surface, revealing they did not elicit osteoblast cytotoxicity. Analyses of four different materials studied with diverse compositions and characteristics showed that adhesiveness was best seen for HA and viability for collagen. In general, the results of this investigation suggest these materials can be used in combination, as scaffolds intended for bone regeneration in dental and medical fields.